Psychoanalysis of Main Character's Personality in The "Kartini" Movie - Suprapto, Suprapto; Mafianto, Ulil; Pramudiyanto, Ahmad (Proceeding of International Joint Conference on UNESA, 2025)
This research focused on analyzing the personality of the main character in the "Kartini" (2017) movie using Sigmund Freud’s psychoanalytic theory. Literature and film served as reflections of human life, highlighting social issues and exploring the complexities of individual personalities and behaviors. The "Kartini" movie portrayed the struggle of Raden Adjeng Kartini for women's rights and education during the colonial era in Indonesia. The method employed in this study was a descriptive method with a qualitative approach. The theoretical framework was based on Sigmund Freud's psychoanalytic theory, particularly his concepts of the id, ego, and superego. The results revealed that Kartini's id was profoundly characterized by her unwavering commitment to advocating for gender equality and educational freedom for women, often disregarding the potential repercussions of her actions. Kartini's ego was evident in her ability to navigate reality and overcome the obstacles she faced in her struggle, including her cleverness in dealing with her older siblings. Lastly, Kartini's superego was demonstrated through her high moral standards and ethical efforts to empower her community and improve the quality of education. This research also discovered that Raden Adjeng Kartini's personality was significantly shaped by her strong will and moral compass, which fueled her fight against traditional societal norms and her advocacy for women's rights. Freud's psychoanalytic approach offered a profound understanding of the motivations and psychological dynamics of the main character in this movie.